DEMOCRACY, POVERTY AND THE SEARCH FOR GOOD GOVERNANCE IN NIGERIA - Morris K.O. EDOGIAWERIE; E.O. Bello (International Studies Journal)
This paper sets out to examine why there is poverty in Nigeria despite the reality that the country is presently practicing and enjoying democracy which is globally adjudged to be the best system of government owing to it progressive and inclusive nature. It is a misnomer for poverty to exist in a democratic state as democracy translates to progress, development and advancement. The existence of poverty indicates that there is no development in the state. So the important question is what is responsible for the profound poverty in Nigeria even as a democratic one? This study will adopt the analytic a priori approach in the exploration of the phenomenon called poverty with a view of determining its cause(s), implications and challenges for the Nigerian state and how to get around this seemingly horrific issue threatening to cripple and tear the nation apart. The work will also focus on exploring the salient elements that characterize good and qualitative governance. Put differently, what is good governance and how can it be attained in a democratic state like Nigeria so much so that poverty can be completely eliminated.